Problems Of Transportation And Traffic Use On The Highway Between The Cities Of Ramadi And Fallujah - Assist. Prof. Dr. Younus Hendi Oleiwi Al-Dulaimi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Evidenced by searching the existence of problems associated with the uses of transport responsible for generating traffic, after standing on the path of the road transport and the medium that its star about a lot of problems, which affect the public safety, the most prominent of accidents and pollution because of its effects on the economic, environmental and social level, then he shed light on the most important proposals, which were addressed based on the opinions that were reached regarding the achievement of the goals of sustainable transport, and then concluded with conclusions and recommendations.